Making knowledge-based services more demandoriented? An experience with ‘public funding, public delivery’ extension in Bénin - GBEHI, CLÉMENT; VERSCHOR, Gerard (My University, 2013)
This article examined newly emerging patterns of agricultural extension in the context of decentralization policy in Bénin. It assesses whether the promises of decentralization were met in the case of the ‘Experimental Development on Innovation’ (EDI) project. Thus, it assessed the extent to which service delivery became demand-oriented and effective in promoting production-enhancing technologies for sustainable agriculture. Semi-structured and individual interviews were used to investigate the dynamics and processes through which the project evolved. The analysis of findings showed that after its promising start, the EDI project experienced a number of setbacks, and eventually became intertwined with the supply-oriented service delivery. While it contended successfully with those involved, consideration must be given to the fact that the formal funding and delivery arrangement often contradicted the expectations that services delivery should become ‘demandoriented’. The article concluded that services delivery depends rather on the negotiation and on the quality of the process in which demand and supply are articulated and matched.
Keywords: Technology transfer; extension service delivery; decentralization; public funding; public delivery; demand-oriented services; demand articulation; Bénin.